Use of Potentially Inappropriate Medications in People With Dementia in Vietnam and Its Associated Factors. Issue 7 (November 2018) - Nguyen, Tuan Anh; Pham, Thang; Vu, Huyen Thi Thanh; Nguyen, Thanh Xuan; Vu, Trinh Thi; Nguyen, Binh Thi Thanh; Nguyen, Ngoc Quynh; Nguyen, Binh Thanh; Nguyen, Binh Thanh; Nguyen, Tam Ngoc; Phan, Sinh Viet; Nguyen, Anh Trung; et al.
This study examined the use of potentially inappropriate medicines that may affect cognition (PIMcog) in people with dementia and its associated factors. Medical records of all outpatients with dementia attending a tertiary hospital in Vietnam between January 1, 2015, and December 31, 2016, were examined. Medicine use was assessed against a list of PIMcog. Variables associated with having a PIMcog were assessed using a multiple logistic regression. Of the 128 patients, 41% used a PIMcog, 39.1% used cholinesterase inhibitors (CEIs) concomitantly with anticholinergics, and 18% used antipsychotics. The number of hospital visits (adjusted odds ratio [OR]: 1.08; 95% confidence interval [CI]: 1.02-1.16) and number of treating specialists (adjusted OR: 0.61; 95% CI: 0.45-0.83) were associated with PIMcog use. This study highlights a high-level use of medicines that can further impair cognition or reduce the effectiveness of CEIs in people with dementia. Efforts to improve quality use of medicines for this population are warranted.